GAMBARAN HISTOPATOLOGI DAN BERAT JANTUNG TIKUS SPRAGUE DAWLEYDUA BULAN PASCA OVARIEKTOMI - , OKI ARDIYANSAH, drh. Rr. Devita Anggraeni, M.P., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to study the heart weight, macroscopic, and histopathologic figure of Sprague-Dawley rat two months after ovariectomy Eightfemale Sprague-Dawley rats at 2 months of age were randomly divided into 2groupsof 4. Group A was sham-operated rats (non-ovariectomy) and group B was ovariectomized was rats. After two months,necropsy was performed to collect the heart. The heart was weighed and kept in neutral buffered formalin solution (NBF) 10% for histopathological examination using haematoxylin eosin staining. The results showed that the heartweight of ovariectomized rats per 100g body weight (0.41 Â± 0.059 g) was not significantly different (P>0.05) compared to sham-operated rats (0.46 Â± 0.051 g). In macroscopic and histopathological figure showed that heart and aorta of ovariectomized rats were not showed any changes. Cardiac muscle cells were still intact in the middle of the nucleus. In the aorta, there was no atheroma plaque formation. In conclusion, ovariectomy had no effect on cardiac figure based on macroscopic, histopathological, and heart weight two months after ovariectomy Keywords : Heart , ovariectomy